Air Fuel Mixing Modeling For Direct And Transfer Port Injection In Two Stroke Engine - Tan, Yee Hern (2013)
Two-stroke engines are commonly found in small transportation units in many South Asian countries. Due to high fuel losses during the scavenging process, the amount of pollution emitted by these two-stroke vehicles is significant. In this study, the details of a gaseous fuel direct injection system using Liquid Petroleum Gas (LPG) were investigated. A series of three-dimensional, Computational Fluid Dynamic (CFD) simulations in ANSYS Fluent are run on various injection geometries, and the air/fuel mixing of the resulting cylinder charge is evaluated. Two approaches for injector installations are investigated in this study. For the first approach, the injector is placed in the engine’s head for direct injection of gaseous fuel into the combustion chamber near the exhaust port closing timing. Many different injector positions and angles are simulated. Technique of splitting fuel plume via flow splitter also being studied to understand the improvement, in which can be done. The second approach is to place the injector in the transfer port window. The injector nozzle is placed in an area where it can directly inject through the transfer port window into the combustion chamber. The simulation is used to understand the injection from different port and the effect of the injector orientation to the amount of fuel leaking into the exhaust port. Several locations and orientations are simulated and the results shows the best combination to install the injector is on the side transfer port with orientation injecting toward the engine head. Experiments had been carried out with the engine setup based on the guideline from simulation and shows 80% decrease in emission and 35.7% decrease in fuel consumption if compare with the baseline carbureted engine.